2020
DOI: 10.1039/d0py00990c
|View full text |Cite
|
Sign up to set email alerts
|

Novel ketone derivative-based photoinitiating systems for free radical polymerization under mild conditions and 3D printing

Abstract: Photopolymerization of acrylates under mild conditions is promising not only for academic research, but also for industrialization applications. However, it still remains a huge challenge to develop effective photoinitiators or...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…In combination with the iodonium salt, the final consumption of ketone−1 was about 78%, while the final consumption of ketone−2 was just 32%. The above steady state photolysis characterizations suggested a strong interaction among the ketone/amine/Iod three−component systems, and an oxidation–reduction photochemical mechanism was already proposed by our group for other photoinitators 21,27 . Moreover, the dramatic difference in the final consumptions of ketones, in the presence of the iodonium salt, indicated that ketone−1 illustrated a much higher photochemical reactivity than ketone−2 under the same irradiation conditions, which could be useful to explain their different photoinitiation abilities for both the free radical polymerization and cationic polymerization.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…In combination with the iodonium salt, the final consumption of ketone−1 was about 78%, while the final consumption of ketone−2 was just 32%. The above steady state photolysis characterizations suggested a strong interaction among the ketone/amine/Iod three−component systems, and an oxidation–reduction photochemical mechanism was already proposed by our group for other photoinitators 21,27 . Moreover, the dramatic difference in the final consumptions of ketones, in the presence of the iodonium salt, indicated that ketone−1 illustrated a much higher photochemical reactivity than ketone−2 under the same irradiation conditions, which could be useful to explain their different photoinitiation abilities for both the free radical polymerization and cationic polymerization.…”
Section: Resultssupporting
confidence: 62%
“…However, for ketone−5 ~ ketone−13, lower ε 405 nm values are observed, which are in a wide range from 900 M −1 cm −1 to 16, 000 M −1 cm −1 . It's believed that the different absorption properties of these ketones would play a very important role in their photoinitiation abilities for the free radical and cationic photopolymerizations 27 …”
Section: Resultsmentioning
confidence: 99%
“…To minimize the negative influence of the well‐known oxygen inhibition effect for free radical polymerization, the photopolymerization of acrylates was performed in laminate upon the irradiation of LED@405 nm (110 mW cm −2 ) at room temperature (the thickness is given in the figure caption). [ 9 ] Typical acrylate function conversion profiles against the LED irradiation time are illustrated in Figure for thin samples. All the photopolymerizations were very fast and reached a plateau within 50 s of LED irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…[161] Besides, at present, their use as photoinitiators of polymerization remains scarce. [162][163][164][165][166] In 2020, the first ferrocene-based chalcones (chalcone 1-chalcone 6) were reported as visible light photoinitiators of polymerization (See Figure 34). Considering that no natural chalcones comprise a ferrocene unit, the six chalcones examined in this work can be considered as bioinspired photoinitiators.…”
Section: Ferrocene-based Chalconesmentioning
confidence: 99%